O princípio da autonomia municipal à luz das transferências intergovernamentais: uma análise de eficiência tributária - Silveira, Kleber Junio (2017)
The Federal Constitution of 1988 configures the political-administrative organization of the Brazilian State, emphasizing the autonomy of the political entities that constitute the Republic and ensuring equal legal and administrative conditions for the Union, the states and the municipalities. When structuring the National Tax System - STN, the CF / 88 establishes the tributes of competence of the federated entities. However, this study shows the dependence of municipal administrations of Ceará from intergovernmental transfers, to the detriment of the federative autonomy through the increase of own revenues. It was decided to use the stochastic frontier methodology of production to estimate the tax efficiency of the municipalities of Ceará, using panel data for the years 2008 to 2014, collected in the "Statistical Yearbook of Ceará", work of IPECE - Instituto de Research and Economic Strategy of Ceará. In the analysis of the tax efficiency of the municipal administrations of Ceará, a "GAP tax" is verified, representing the difference between the potential and the effective collection, estimated based on the stochastic frontier of measured production. In the analysis, it should be noted that 97 municipalities in Ceará have exceeded the average fiscal effort, while the remaining 87 municipalities performed below the average fiscal effort index. It is evidenced the concentration of the collection in the municipalities of the Metropolitan Region of Fortaleza. It can be concluded that there is an expressive growth potential of the own tax collection of the municipalities of Ceará, if administrative decisions were adopted aiming at the attainment of autonomy.